High Selectivity of 8-Hydroxyquinoline on Leishmania (Leishmania) and Leishmania (Viannia) Species Correlates with a Potent Therapeutic Activity In Vivo - Lima, Sarah Kymberly Santos de [UNESP]; Jesus, Jéssica Adriana [UNESP]; Raminelli, Cristiano; Laurenti, Márcia Dalastra; Passero, Luiz Felipe Domingues [UNESP] (MDPI, 2023)
Leishmaniasis is a neglected disease caused by protozoa of the genus Leishmania, which causes different clinical manifestations. Drugs currently used in the treatment such as pentavalent antimonial and amphotericin B cause severe side effects in patients, and parasite resistance has been reported. Thus, it is necessary and urgent to characterize new and effective alternative drugs to replace the current chemotherapy of leishmaniasis. In this regard, it has been experimentally demonstrated that quinoline derivatives present significative pharmacological and parasitic properties. Thus, the aim of this work was to demonstrate the leishmanicidal activity of 8-hydroxyquinoline (8-HQ) in vitro and in vivo. The leishmanicidal activity (in vitro) of 8-HQ was assayed on promastigote and intracellular amastigote forms of L. (L.) amazonensis, L. (L.) infantum chagasi, L. (V.) guyanensis L. (V.) naiffi, L. (V.) lainsoni, and L. (V.) shawi. Additionally, the levels of nitric oxide and hydrogen peroxide were analyzed. The therapeutic potential of 8-HQ was analyzed in BALB/c mice infected with a strain of L. (L.) amazonensis that causes anergic cutaneous diffuse leishmaniasis. In vitro data showed that at 24 and 72 h, 8-HQ eliminated promastigote and intracellular amastigote forms of all studied species and this effect may be potentialized by nitric oxide. Furthermore, 8-HQ was more selective than miltefosine. Infected animals treated with 8-HQ by the intralesional route dramatically reduced the number of tissue parasites in the skin, and it was associated with an increase in IFN-γ and decrease in IL-4, which correlated with a reduction in inflammatory reaction in the skin. These results strongly support the idea that 8-HQ is an alternative molecule that can be employed in the treatment of leishmaniasis, given its selectivity and multispectral action in parasites from the Leishmania genus.
Keywords: cutaneous leishmaniasis; leishmaniasis; treatment